2017
DOI: 10.1590/1983-21252017v30n106rc
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea Growth and Yield in Sole Crop and Intercropped With Millet

Abstract: -The objective of this work was to evaluate the growth and yield of cowpea grains in different intercropping systems with millet, in wet and dry seasons. The experiments were performed in the experimental field of the Department of Plant Science of the Federal Rural University of Rio de Janeiro, Brazil, using a randomized block design with three replications and five treatments: T1-sole crop of millet; T2-sole crop of cowpea; T3-intercrop of millet (1 row) and cowpea (1 row) with 0.5 m between rows (1Mx1C-0.50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Oliveira et al. (2017) observed that cowpea in consortium with millet presented a nodule dry mass equal to the monoculture system, showing that the millet‐generated shading did not affect nodulation, similar to the tree component and buffel grass in the present study. Similar results were also observed by Silva et al.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Oliveira et al. (2017) observed that cowpea in consortium with millet presented a nodule dry mass equal to the monoculture system, showing that the millet‐generated shading did not affect nodulation, similar to the tree component and buffel grass in the present study. Similar results were also observed by Silva et al.…”
Section: Resultssupporting
confidence: 73%
“…Correia et al (2021) determined that artificial shading with a shade screen did not influence the number of nodules and nodules dry mass variables in flowering cowpea compared to unshaded cultivation, corroborating the results of the present study as the distance from the eucalyptus planting rows did not change the nodulation variables. Oliveira et al (2017) observed that cowpea in consortium with millet presented a nodule dry mass equal to the monoculture system, showing that the millet-generated shading did not affect nodulation, similar to the tree component and buffel grass in the present study. Similar results were also observed by Silva et al (2016) in single cowpea cultivation and cowpea intercropped with Brachiaria decumbens.…”
Section: Growth Production Nodulation and Physiological Characteristi...supporting
confidence: 70%
“…Mohamed (2007) stated that root dry weight was higher in sole cropping than intercropping with sorghum. Oliveira et al (2017) stated that root dry weight of cowpea is not significantly affected, when cowpea intercropped with millet.…”
Section: Dry Weight Of Rootmentioning
confidence: 99%
“…Pennisetum glaucum (L.) R. Brown is a traditional crop in West Africa and Asia, with exceptional adaptation to abiotic stresses [13]. It is one of the most cultivated cover crop species in the Cerrado region due to its greater tolerance to drought, high biomass production and efficient nutrient cycling [8,14,15], and it is adapted to semi-arid regions [16].…”
Section: Introductionmentioning
confidence: 99%